Cephalosporin-resistant typhoid. (April 2020) - Pereira, Noella Maria Delia; Shah, Ira
Typhoid fever is endemic in developing countries like India. An increasing prevalence of resistance to cephalosporins and fluoroquinolones by Salmonella isolates is seen. We present an 8-month-old boy with invasive Salmonella typhi disease. Blood culture showed S. typhi sensitive to ampicillin–sulbactam and cotrimoxazole but resistant to fluoroquinolones and third-generation cephalosporins. Cerebrospinal fluid examination revealed an aseptic meningitic picture. He was treated with intravenous meropenem and azithromycin following which his condition improved. This case highlights the need for improvement in environment sanitation and hygiene combined with early vaccination against typhoid fever and antimicrobial stewardship to help reduce the emerging resistance to cephalosporins and fluoroquinolones.